A View from the European Poets "Windows" (an Attempt on Comparative Analysis of "Windows" by Stephane Mallarme and Gustaw Danilowski) - Legutko, Grażyna (Respectus Philologicus, 2006)
The article presents a comparative analysis of two poems written by French and Polish poets, titled exactly the same "Windows". Both are a poetical notation of an effort to seek the sense of human existence and an attempt to solve a vague riddle of existence. Although Stephane Mallarme and Gustaw Danilowski are authors from two different countries, they have common convictions, which are close to the idealistic outlook on the life of European Symbolists. Because of their similar views, the subject of their poems has analogical problems. Lyrical subjects narrate the pain, suffering, despair and the crudeness of human existence; they long to break out from the circle of human existence; they dream of escape from everyday life and reach the sphere of infinity ( the absolute )."Windows" are the mysterious borderline between earthly and extraterrestrial life for both poets. The meaning of both "Windows" is symbolic: Mallarrne associates them with art and dream, while Danilowski associates them with a mystical vision.
Keywords: symbolism; European modernism; Young Poland's poetry; transcendence; the absolute; death; extraterrestrial life; mysticism; symbolic outlook on life